Clinicopathological and Molecular Specificities of Inflammatory Bowel Disease–Related Colorectal Neoplastic Lesions: The Role of Inflammation. (10th September 2018) - Svrcek, Magali; Borralho Nunes, Paula; Villanacci, Vincenzo; Beaugerie, Laurent; Rogler, Gerhard; De Hertogh, Gert; Tripathi, Monika; Feakins, Roger; ,
Abstract: Compared with the general population, patients with inflammatory bowel disease [IBD] have an increased risk of developing colorectal cancer. Molecular mechanisms underlying colorectal carcinogenesis in the setting of IBD are not well understood. However, modern molecular investigative tools have facilitated the identification of features that help distinguish IBD-related carcinoma from sporadic carcinoma. Moreover, with advances in endoscopic technology and improved understanding of the natural history, the management of colorectal neoplastic lesions in IBD patients has evolved. This review discusses the clinicopathological and molecular features of colorectal neoplastic lesions complicating IBD. Chronic inflammation is believed to promote the development of neoplasia, partly by producing reactive oxygen and nitrogen species [ROS and NOS], which may interact with genes involved in carcinogenetic pathways. Furthermore, alterations in microbiota and in the innate and adaptive immune responses might contribute to this process, particularly by initiating, regulating, and sustaining chronic inflammation. Earlier detection and better characterization of neoplastic colorectal lesions complicating IBD and a better knowledge of the molecular mechanisms underlying carcinogenesis in this setting should facilitate improvements in the risk stratification of patients with longstanding IBD and in the management of dysplastic and malignant colorectal lesions that arise in this setting.